2012
DOI: 10.1124/jpet.112.194340
|View full text |Cite
|
Sign up to set email alerts
|

Δ-9,11 Modification of Glucocorticoids Dissociates Nuclear Factor-κB Inhibitory Efficacy from Glucocorticoid Response Element-Associated Side Effects

Abstract: Glucocorticoids are standard of care for many inflammatory conditions, but chronic use is associated with a broad array of side effects. This has led to a search for dissociative glucocorticoidsdrugs able to retain or improve efficacy associated with transrepression [nuclear factor-B (NF-B) inhibition] but with the loss of side effects associated with transactivation (receptor-mediated transcriptional activation through glucocorticoid response element gene promoter elements). We investigated a glucocorticoid d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Studies have suggested that these anti-inflammatory effects of this class of drugs may be mediated by the inhibition of the anti-inflammatory NF-kB activity [15,16]. Recently, the NF-kB inhibitory activity of two 21-aminosteroids, anecortave and VBP15, were found to be dependent on binding to the glucocorticoid receptor, contrary to previous models of the mechanism of action of this class of drugs [14,17,18]. We sought to determine if the clinically developed 21-aminosteroid, lazaroid U-74389G, also showed GR-dependent NF-kB inhibitory activity, and if this drug inhibited osteoblastic differentiation in AVICs.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies have suggested that these anti-inflammatory effects of this class of drugs may be mediated by the inhibition of the anti-inflammatory NF-kB activity [15,16]. Recently, the NF-kB inhibitory activity of two 21-aminosteroids, anecortave and VBP15, were found to be dependent on binding to the glucocorticoid receptor, contrary to previous models of the mechanism of action of this class of drugs [14,17,18]. We sought to determine if the clinically developed 21-aminosteroid, lazaroid U-74389G, also showed GR-dependent NF-kB inhibitory activity, and if this drug inhibited osteoblastic differentiation in AVICs.…”
Section: Introductionmentioning
confidence: 80%
“…U-74389G has been clinically developed as a potential drug to protect against ischemia/ reperfusion injury of the central nervous and liver, but did not achieve regulatory approval [11,12]. The use of antioxidants in inflammatory diseases has been widely advocated and studies suggested that U-74389G and other 21-aminosteroids are potent inhibitors of the synthesis of several pro-inflammatory cytokines, such as IL-6, IL-8, interferon-g (IFN-g) and tumor necrosis factor-a (TNF-a) [13,14]. Studies have suggested that these anti-inflammatory effects of this class of drugs may be mediated by the inhibition of the anti-inflammatory NF-kB activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This compound, similar to the full GR agonist DEX and other dissociated GCs [38,[41][42][43][44] has been demonstrated to inhibit the LPS/IFN-γ mediated NO formation in a concentrationdependent manner and to repress NOS-2 and COX-2 gene expression in macrophages. 21OH-6,19OP also inhibits TNF-α-induced COX-2 and IL-8 expression in human lung cancer A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it was demonstrated that VBP1, a Δ-9,11 analog, was more effective than full agonists, to down-regulate anti-inflammatory genes whose promoters contain both GREs and NF-κB promoter elements, probably due to incapacity of the GR to directly bind DNA [44]. This would not be the case for this rigid compound, since GR/21OH-5,19OP…”
mentioning
confidence: 98%
See 1 more Smart Citation